Penilaian Kinerja Koperasi dalam Perspektif Hukum Positif di Indonesia - Noubel Putra Nainggolan; Febryanti Angkat; Yohana Feby; Khairani Alawiyah Matondang (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to explore how Indonesia's auspicious legal framework supports the establishment and functionality of cooperatives and identify challenges to its implementation. Used in this study is a qualitative Systematic Literature Review (SLR), whose collection and review of literature were conducted through various academic sources with complementary legislation. The results of the research indicate that in spite of the existence of formal arrangements and rules for institutional factors and cooperative health assessments, field practice is weak due to lack of understanding, socialization, and effective supervision. Social and geographical diversity and legal limitations are also major concerns in the realization of adaptive and sustainable cooperatives. Therefore, the regulatory approach has to be reformed and the institutional strength of cooperatives increased to guarantee more effective functioning as well as in accordance with cooperative principles.